Information technology outsourcing - Rivard, Suzanne; Aubert, Benoit A. (Advances in management information systems ;, 2008)
"This new volume in the Advances in Management Information Systems series presents the latest cutting-edge knowledge in IT outsourcing. As part of the growing business trend to outsourcing various operations, IT outsourcing both determines the governance of a vital organizational function and influences the processes of exploitation and exploration in all other functions of an enterprise. In keeping with the mission of the AMIS series, the editors of this volume have framed the domain of research and practice broadly. Information Technology Outsourcing provides leading edge research on both the variety of decisions regarding the outsourcing of IS services and the management of the relationship with service suppliers"--Provided by publisher